Javanese Traditional Menu and Bedaya Dance as the Cultural Tourism Attractions of Magersari and Yogyakarta Kingdom - Nurhayati, Endang; Suharti, -; Andayani, Rahmi D (LPPM UNY, 2015)
This study aimed to describe the characteristics of the types of the dinner menu and entertainments that are served to tourists in restaurants, at cultural tourism area of Yogyakarta Kingdom. This study used qualitative methods, and ethnocultural theory approach. The results show that Javanese ethnic (in this case represented by Yogyakarta Kingdom cultural tourism entrepreneurs) presents dishes and typical dance heritage that are 'market table'. The dishes are sega golong, sekul ijo, singgang panggang, bebek suwir, semur piyik, urip-urip gulung, sanggar, sup timlo, pandekuk, prawan kenes, randha tapa, tapak kucing, manuk nom, burdedeg, and bendul with typical drink like Javanese beer and wedang secang. The entertainments showed are Kakung dance and Putri dance